Development of systolic dysfunction unrelated to myocardial infarction in treated hypertensive patients with left ventricular hypertrophy. The LIFE Study - Marcello Chinali; Gerard P. Aurigemma; Eva Gerdts; Kristian Wachtell; Peter M. Okin; Anujan Muthiah; Sverre E. Kjeldsen; Stevo Julius; Giovanni de Simone; Richard B. Devereux (Open Exploration Publishing Inc., 2022)
Aim: While it is commonly thought that left ventricular (LV) systolic function may insidiously deteriorate in hypertensive patients, few prospective data are available to support this notion. Methods: We evaluated 680 hypertensive patients (66 ± 7 years; 45% women) with electrocardiographic (ECG)-LV hypertrophy (ECG-LVH) enrolled in the Losartan Intervention For Endpoint reduction in hypertension (LIFE) echo-sub-study free of prevalent cardiovascular disease and with baseline ejection fraction (EF) ≥ 55%. Echocardiographic examinations were performed annually for 5 years during anti-hypertensive treatment. Development of reduced systolic function was defined as incident EF < 50%. Results: During a mean follow-up of 4.8 ± 1 years, 37 patients developed reduced EF without an inter-current myocardial infarction (5.4%). In analysis of covariance, patients who developed reduced EF were more often men, had greater baseline LV diameter and LV mass, lower mean EF (all P < 0.05), and similar diastolic function indices. At the last available examination before EF reduction, independently of covariates, patients with reduced EF showed a significant increase in left atrium (LA) size, LV diameter, end-systolic stress and mitral E/A ratio, as compared to those who did not develop reduced EF (all P < 0.05). In time-varying Cox regression analysis, also controlling for baseline EF, predictors of developing reduced EF were higher in-treatment LV diameter [hazard ratio (HR) = 5.19 per cm; 95% confidence interval (CI): 2.58-10.41] and higher in-treatment mitral E/A ratio (HR = 2.37 per unit; 95% CI: 1.58-3.56; both P < 0.0001). Conclusions: In treated hypertensive patients with ECG-LVH at baseline, incident reduced EF is associated with the development of dilated LV chamber and signs of increased LV filling pressure (ClinicalTrials.gov identifier: NCT00338260).